A Kolmogorov type criterion for the best approximating operator - Tyrygin, I. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For the best approximating operator, a criterion is established, equivalent to the well known Kolmogorov theorem, which characterizes the best approximation element. The practical use of this criterion is illustrated by examples.